Regiones de economía abierta y cerrada - Daher, Antonio (El Colegio de México A.C., 1993)
This study identifies the regions of Chile that produce goods, both for the domestic market and for export, after a decade and a half of the implementation of a new development model. It examines the different degrees to which the regional markets opened and their unequal contribution to international trade.The regional "specialization" is contrasted with the divergent territorial distribution of investments in goods and service industries; these, especially those oriented toward exports, have become important sources of differentiation -indeed, discrimination- among regions.The export or domestic specialization of the region presents markedly different regional vulnerabilities with respect to the fluctuations of the market -local and international- and with respect to macroeconomic and international trade policies.